2021
DOI: 10.1253/circj.cj-20-1115
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Kidney Disease on In-Hospital and 3-Year Clinical Outcomes in Patients With Acute Myocardial Infarction Treated by Contemporary Percutaneous Coronary Intervention and Optimal Medical Therapy ― Insights From the J-MINUET Study ―

Abstract: Background:The impact of chronic kidney disease (CKD) on long-term outcomes following acute myocardial infarction (AMI) in the era of modern primary PCI with optimal medical therapy is still in debate. Methods and Results:A total of 3,281 patients with AMI were enrolled in the J-MINUET registry, with primary PCI of 93.1% in STEMI. CKD stage on admission was classified into: no CKD (eGFR ≥60 mL/min/1.73 m 2 ); moderate CKD (60>eGFR≥30 mL/ min/1.73 m 2 ); and severe CKD (eGFR <30 mL/min/1.73 m 2 ). While the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…In this study, the number of EI strategies was 85.8% (7073/8241), which may be related to the effects of the preference of the current guidelines [6,22] for EI strategy rather than DI strategy, and the participation of a higher number of tertiary hospitals (more than 50 community and teaching hospitals) in South Korea [33]. Compared to younger non-CKD patients with less mature plaques that are more vulnerable to rupture, patients with CKD tend to be older and have more established atherosclerosis, and plaque erosion is a major substrate for coronary thrombosis [34]. Despite the current guidelines [6,22] recommendations that an EI strategy is reasonable for the initially stabilized high-risk patients with NSTE-ACS, comparative studies between the EI and DI strategies confined to patients with NSTEMI and CKD, who received newer-generation DES, were very limited and their results were debatable.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the number of EI strategies was 85.8% (7073/8241), which may be related to the effects of the preference of the current guidelines [6,22] for EI strategy rather than DI strategy, and the participation of a higher number of tertiary hospitals (more than 50 community and teaching hospitals) in South Korea [33]. Compared to younger non-CKD patients with less mature plaques that are more vulnerable to rupture, patients with CKD tend to be older and have more established atherosclerosis, and plaque erosion is a major substrate for coronary thrombosis [34]. Despite the current guidelines [6,22] recommendations that an EI strategy is reasonable for the initially stabilized high-risk patients with NSTE-ACS, comparative studies between the EI and DI strategies confined to patients with NSTEMI and CKD, who received newer-generation DES, were very limited and their results were debatable.…”
Section: Discussionmentioning
confidence: 99%
“…Renal function appears to play a major role in prognosis of patients with impaired renal function. Furthermore, Hashimoto and Ozaki and his coworkers recently reported that 3-year mortality and MACE significantly deteriorated from 5.09% and 15.8% in no CKD through 16.3% and 38.2% in moderate CKD to 36.7% and 57.9% in severe CKD, respectively ( p < 0.0001), based on 3,281 patients with AMI enrolled in the J-MINUET registry associated with primary PCI of 93.1% in STEMI [ 197 ]. They concluded that CKD remains a useful predictor of in-hospital and 3-year mortality as well as MACE after AMI in the modern PCI and optimal medical therapy era [ 197 ].…”
Section: Practical Recommendation For Primary Pcimentioning
confidence: 99%
“…Furthermore, Hashimoto and Ozaki and his coworkers recently reported that 3-year mortality and MACE significantly deteriorated from 5.09% and 15.8% in no CKD through 16.3% and 38.2% in moderate CKD to 36.7% and 57.9% in severe CKD, respectively ( p < 0.0001), based on 3,281 patients with AMI enrolled in the J-MINUET registry associated with primary PCI of 93.1% in STEMI [ 197 ]. They concluded that CKD remains a useful predictor of in-hospital and 3-year mortality as well as MACE after AMI in the modern PCI and optimal medical therapy era [ 197 ]. Recently, Collet JP and the task force for the management of ACS of the European Society of Cardiology (ESC) recommended in patients with atrial fibrillation and high bleeding risk, triple antithrombotic therapy with DOAC, aspirin, and clopidogrel should be given in a short period up to 1 week followed by double therapy using DOAC and clopidogrel for 6 months then DOAC monotherapy after the 6 months, while in those with atrial fibrillation and high ischemic risk, triple antithrombotic therapy including DOAC, aspirin, and clopidogrel should be provided up to 1 month followed by double therapy consisting of DOAC and clopidogrel for 12 months then DOAC monotherapy after the 12 months [ 21 ].…”
Section: Practical Recommendation For Primary Pcimentioning
confidence: 99%
“…Walter et al [39] found that patients receiving prolonged statin treatment developed lower in-stent restenosis rates in comparison with nonreceivers (25% vs. 38%). Therefore, our results showing similar re-MI and any repeat revascularization rates between statin users and nonusers could be related to low number of enrolled patients in groups A4, B1, B3 and B4 and relatively low incidences of these events compared with previous studies [17,30]. According to recent meta-analysis data that evaluated CKD patients [40], in which CKD was defined as eGFR < 60 mL/min/1.73 m 2 , results showed that the TLR/TVR (RR, 0.69; 95% CI, 0.57-0.84) was significantly reduced with DESs compared with bare-metal stents (BMS).…”
Section: Discussionmentioning
confidence: 48%
“…Patients with CKD are often excluded from randomized trials that evaluate cardioprotective drugs, and the quality and coverage of evidence on which to guide decision making in this population is suboptimal [29]. This lack of evidence on optimal treatment strategies for such patients may result in worse outcomes [30]. Additionally, the cause of CD is influenced by misclassification of their atypical clinical presentation [31].…”
Section: Discussionmentioning
confidence: 99%